The history of interethnic relations in Uzbekistan - Khusanov, Khabibullo (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
In this article the essence and relationship between concepts national interest and the international relations in the conditions ofglobalization in public life is investigated. It is considered that the foundations of any international relation make national interests , theircontent and its socio-political role